2008
DOI: 10.1111/j.1529-8019.2008.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Local antibiotics in dermatology

Abstract: Although the vast majority of skin infection must be treated with systemic antibiotics, topical antibiotics are used overwhelmingly in the world, often as self-prescribed medications without taking into account the sensitivity of the presumed bacteria. Dermatologists are aware that different types of topical antibiotics kill different species of bacteria and tend to be more specific in their prescriptions. At present local antibiotics are advised to treat minor superficial uncomplicated skin infections (e.g., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 30 publications
0
40
0
8
Order By: Relevance
“…However when the skin's natural defence weakens accidentally or intentionally, the role for antibacterials emerge. Most antibacterials used topically offer several advantages, such as avoidance of systemic toxicity leading to fewer side effects, decreased induction of bacterial resistance, and the high concentration of antibacterial agent at the site of infection [8]. One good example is mupirocin (pseudomonic acid A), an antibiotic produced by Pseudomonas fluorescens which has been shown to possess high activity against staphylococci, streptococci, and certain Gram-negative bacteria such as Neisseria gonorrhoeae and Haemophilus influenza [9].…”
Section: Introductionmentioning
confidence: 99%
“…However when the skin's natural defence weakens accidentally or intentionally, the role for antibacterials emerge. Most antibacterials used topically offer several advantages, such as avoidance of systemic toxicity leading to fewer side effects, decreased induction of bacterial resistance, and the high concentration of antibacterial agent at the site of infection [8]. One good example is mupirocin (pseudomonic acid A), an antibiotic produced by Pseudomonas fluorescens which has been shown to possess high activity against staphylococci, streptococci, and certain Gram-negative bacteria such as Neisseria gonorrhoeae and Haemophilus influenza [9].…”
Section: Introductionmentioning
confidence: 99%
“…All these may explain why fusidic acid appeared to be the most frequent dispensed topical antibacterial drugs in Kedah state. However, studies had shown that increased and prolonged usage of topical fusidic acid treatment had led to the increase of antibacterial resistance rates which stressed the judicious use of topical antibacterial drugs by healthcare professional especially CPs [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…В табл. 1 даны разъяснения о месте локальной и системной антибиотикотерапии в лечении инфици-рованных ран [14,15].…”
Section: антисептикиunclassified
“…В теории с уве-личением площади и кратности нанесения таких пре-паратов увеличивается и риск системного действия [20][21][22]. И хотя подобных исследований не проводи-лось, хирурги в амбулаторных условиях не используют местные антибактериальные препараты на больших площадях (более 10 % поверхности тела) [15,19]. В по-добных ситуациях приоритет имеют растворы анти-септиков с их неселективным действием на флору [4].…”
Section: антисептикиunclassified
See 1 more Smart Citation